(untitled) (Research, Society and Development, 2020)
The present study aimed to assess the hygienic and sanitary quality of restaurants in a public market regarding the handlers of foods, fruits & vegetables and ready-to-eat foods. This is a descriptive and cross-sectional study, approved by the Research Ethics Committee, performed in 2019 in restaurants (n=15) from a public market in a capital of the Brazilian Northeast. We applied a checklist of good food manufacturing practices, adapted from the Brazilian regulatory standards, containing 23 items referring to the categories of food handlers, hygiene of fruits & vegetables as well as prepared foods. Data were assessed and classified according to the compliance with high, medium or low adequacy items. In order to check associations among variables, we used the Chi-square or the Fisher’s exact test, and the level of significance was p<0.05. The results showed that most of the evaluated items were inadequacies regarding the Brazilian health standards, with a statistically significant difference (p<0.05). In the global assessment of the categories, we found that only 40% of the items were adequate, with a statistically significant difference regarding the inadequacies. Therefore, the assessed restaurants have inadequate hygienic and sanitary conditions in the production of meals and need an intervention action, since this sanitary fragility endangers the health of consumers.